Pengaruh Konten Promosi, Online Customer Riview, Online Customer Rating Terhadap Keputusan Pembelian Produk Cosmetic Skintific di E-Commerce Shopee - Putri Sadila; Murwanti, Sri (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to examine the influence of promotional content, online customer reviews, and online customer ratings on purchasing decisions for Skintific cosmetic products on the Shopee e-commerce platform in the Soloraya region. A quantitative approach with a descriptive design was used, and the sample consisted of 150 respondents selected using purposive sampling. Data were collected through an online questionnaire using the Likert scale to measure respondents' perceptions of the variables under investigation. The results indicate that promotional content has a positive but insignificant effect on purchasing decisions, while online customer reviews and online customer ratings have a positive and significant effect on purchasing decisions. The study recommends adding variables such as brand image and influencer marketing and maintaining the quality of Skintific products to sustain consumer interest.